韓國型 出血熱 IX . 병원체 (病原體) 한탄 (漢灘)바이러스를 접종한 (接種) Albino마우스에서의 免疫글로불린 形成에 關한 硏究 - 주용규; 朱容奎; 백락주; 白樂柱; 성인화; 成仁華; 이용주; 李容周; 이호왕; 李鎬汪 (Journal of bacteriology and virology, 1982)
In this study albino mice were inoculated with different strains of Hantaan virus intramuscularly which were propagated in different host cells and found that strain of the virus propagated in Vero cells produced good antibody response in the mice. 1. Immunoglobulin G against Hantaan virus antigen was started to appear on 5th day after inoculation of the virus, reached maximun on 2nd to 3rd week and kept for 2 weeks and then declined slowly. 2. Immunoglobulin M to the virus was started to appear on 9th day after inoculation and reached maximum on 2nd to 3rd week and kept for 2 weeks and then declined slowly and disappeared around 5th week after inaculation of the virus. 3. Immunoglobulin A to the virus was not demonstrated at all in the mice.